Updating and expanding systematic reviews and meta‐analyses on the effects of school‐wide positive behavior interventions and supports - Lee, Ahhyun; Gage, Nicholas A. (Psychology in the schools, 2020)
School‐wide positive behavior interventions and supports (SWPBIS) is a multitiered support framework for preventing problem behaviors and increasing prosocial behaviors. There has been an increasing number of experimental group design research studies focused on the impacts of SWPBIS. Therefore, we conducted a systematic review to update and extend prior reviews by including both published and unpublished studies and conducting a robust variance estimation meta‐analysis to examine the magnitude of the effect of SWPBIS on all available school‐level outcomes. A total of 29 studies were identified across the United States and Europe, including seven randomized controlled trials and 22 quasi‐experimental group design studies. Overall, statistically significant reductions in school discipline and increased academic achievement were found. Effect sizes were small to medium. Limitations and implications are discussed.